EDUKASI TENTANG MANFAAT BABY SPA UNTUK PERTUMBUHAN DAN PERKEMBANGAN BAYI BERBASIS ONLINE - Arfiani, Arfiani; Khatimah, Husnul; Nurazira (JCS, 2024)
Babies are children with an age range of 0-12 months. The process of optimal growth and development for children is very important in shaping their personalities as high quality and tough individuals. According to the Indonesian Ministry of Health, around 16% of babies in Indonesia experience growth disorders. So it is necessary to provide education regarding the benefits of baby massage, with the aim of the community and mothers being able to understand baby massage so that later the community, especially mothers, will be able to apply it to babies and toddlers in order to optimize their growth and development and improve their health status. This activity was carried out on Wednesday 20 September 2023 in the framework of AKTABE's XVth Anniversary using the midwifery scientific webinar method consisting of lectures, discussions and questions and answers online via media (zoom). The results of the service showed that community service education activities about the benefits of baby spas for the growth and development of babies using this online method really helped the community increase their knowledge, especially regarding baby massage.